2018
DOI: 10.3389/fncel.2018.00470
|View full text |Cite
|
Sign up to set email alerts
|

Synaptopathology Involved in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) encompasses a group of multifactorial neurodevelopmental disorders characterized by impaired social communication, social interaction and repetitive behaviors. ASD affects 1 in 59 children, and is about 4 times more common among boys than among girls. Strong genetic components, together with environmental factors in the early stage of development, contribute to the pathogenesis of ASD. Multiple studies have revealed that mutations in genes like NRXN, NLGN, SHANK, TSC1/2, FMR1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
180
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(188 citation statements)
references
References 221 publications
(237 reference statements)
4
180
0
4
Order By: Relevance
“…Our study revealed relatively high susceptibility of the CA1 hippocampal area to PPA treatment. Molecular, histological and biochemical data also point out the altered CA1 area in PPA and other autism models (Dahlhaus et al, 2010;Guang et al, 2018;MacFabe et al, 2007). The special vulnerability of this region to various neuropathological conditions (epilepsy, depression, encephalitis, stroke, limbic encephalitis, hypoglycaemic encephalopathy, multiple sclerosis, transient global amnesia, Alzheimer disease, etc.)…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our study revealed relatively high susceptibility of the CA1 hippocampal area to PPA treatment. Molecular, histological and biochemical data also point out the altered CA1 area in PPA and other autism models (Dahlhaus et al, 2010;Guang et al, 2018;MacFabe et al, 2007). The special vulnerability of this region to various neuropathological conditions (epilepsy, depression, encephalitis, stroke, limbic encephalitis, hypoglycaemic encephalopathy, multiple sclerosis, transient global amnesia, Alzheimer disease, etc.)…”
Section: Discussionmentioning
confidence: 97%
“…Autism spectrum disorders (ASDs) are highly heritable, complex and pervasive conditions, characterized by communication deficits, restricted interests, emotional problems and cognitive impairments. Many genes traditionally thought to be involved in autism encode cell adhesion molecules and proteins involved in neurogenesis, synaptogenesis, synaptic functions and other cellular processes (Chen, Chang, & Huang, ; Guang et al, ; Zhao et al, ). In addition to the genetic component, a number of environmental factors participate in autism pathogenesis, affecting synapse activities, neuroimmune regulation, gastrointestinal function, metabolism and gene expression (Choi et al, ; Huang & Jin, ; MacFabe, ; Rizzetto, Fava, Tuohy, & Selmi, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E:I balance governs the output of neurons based on the local level of excitatory/inhibitory synaptic transmission and intrinsic excitability. Some of the highest confidence ASD-risk genes encode proteins that directly impact E:I balance (4,5) and multiple animal models display synaptic transmission deficits alongside ASD-like behavioral abnormalities (2,(6)(7)(8)(9)(10)(11)(12). E:I balance is sustained through homeostatic plasticity mechanisms that maintain network activity within an optimal range by tuning synaptic strength (13) and intrinsic excitability (14).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that changes in calcium signaling may be associated with ASD [43][44][45]. Similarly, multiple studies support a link of immune dysfunction and inflammation to ASD [46][47][48], while strong evidence exists for a link with synaptic structures [49][50][51][52]. Upregulation of immune genes and downregulation of synaptic genes was observed in the postmortem brains of idiopathic ASD patients [53,54].…”
Section: Discussionmentioning
confidence: 95%